New insights into pathways that determine the link between infection and thrombosis - Levi, M; van der Poll, T; Schultz, M (Netherlands journal of medicine, 2012)
Severe infection is often linked to prothrombotic events. Indeed, haemostatic abnormalities are encountered in most cases of infection, ranging from an increase in sensitive markers for coagulation activation or insignificant laboratory changes to gross activation of coagulation that may result in localised thrombotic complications or disseminated intravascular coagulation. Systemic inflammation as a consequence of infection results in activation of coagulation, due to tissue factor-mediated thrombin generation, down-regulation of physiological anticoagulant mechanisms, and inhibition of fibrinolysis. Pro-inflammatory cytokines, immune cells and the endothelium form the interface on which differential effects on the coagulation and fibrinolysis pathways may ensue. Conversely, activation of the coagulation system may importantly affect inflammatory responses by direct and indirect mechanisms. Apart from the general coagulation response to inflammation associated with severe infection, specific infections may cause distinct features, such as haemorrhagic fever or thrombotic microangiopathy.